Development and validation of an analytical method for trace‐level quantification of genotoxic nitrosamine impurities in losartan and hydrochlorothiazide fixed‐dose combination tablets using ultra performance liquid chromatography triple quadrupole mass spectrometry. (21st February 2023) - Patel, Ravi; Purohit, Sanjay; Solanki, Ravisinh; Khunt, Dignesh; Patel, Chhaganbhai; Patel, Rucha; Parikh, Shalin
Abstract: Rationale: Since June 2018, globally large numbers of pharmaceuticals have been recalled due to the unexpected presence of nitrosamines. Beginning with the class of pharmaceuticals known as sartans, subsequent lines of inquiry included antidiabetic medicines, antihistamines, and antibiotics. A critical review of the U.S. Food and Drug Administration database reveals that the highest number of products recall due to the presence of unacceptable levels of nitrosamines were losartan potassium drug products and their coformulations with other drug substances. The problem can be mainly attributed to naively adopted approval revisions and the lack of sufficient current analytical technologies to detect those contaminants in time. In this work, we developed a specific, selective, accurate, precise, and robust ultra‐performance liquid chromatography‐triple quadrupole‐mass spectrometry (UPLC‐TQ‐MS/MS) method for the estimation of eight genotoxic nitrosamine impurities in losartan and hydrochlorothiazide (HCTZ) tablets, which is the only fixed‐dosage combination approved by the USFDA to treat hypertension. Methods: All the nitrosamine impurities along with the drug substances were separated using an Agilent Pursuit XRs Ultra diphenyl column (150 × 2.0 mm, 2.8 μm) with mobile phase A (0.1% formic acid in water) and mobile phase B (0.1% formic acid in methanol) at a flow rate of 0.4 ml/min using the gradient elution program. The proposed method was validated per ICH (International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use) Q2 (R1) guidelines to ensure the method is suitable for its intended purpose. Results: Limit of detection and limit of quantification were obtained in the range of 0.25–0.5 ng/mL, which was very low compared to levels specified by the USFDA, European Medicines Agency (EMA), and other regulatory authorities that ensure the sensitivity of the method in its entire life cycle. Conclusions: The developed method can be incorporated into an official monograph and applied for routine quality control analysis of losartan and HCTZ fixed‐dose combination tablets.